Two new species of Alphonsea (Annonaceae) from Thailand - Leeratiwong, Charan; Chalermglin, Piya; Johnson, David M. (Phytotaxa, 2020)
Two new species of Alphonsea (Annonaceae) from Thailand, A. longicarpa and A. phuwuaensis are described and illustrated.